Manejo de la vía venosa periférica por parte del personal de enfermería en los servicios de medicina interna, gineco obstetricia, pediatría y cirugía del hial, 2013 - Rojas Carrión, Dayana Mariuxi (2014)
The present study is of descriptive type and she has as purpose to characterize the procedure of the cateterización of the outlying veined road carried out by 27 nurses that work in the services of Internal Medicine, Gineco - Obstetrics, Pediatrics and Surgery of the Hospital Isidro Ayora of Loja the 2013, to which were carried out three observations and identification of the derived more frequent complications of the procedure in patients assisted in these services, the results point out that the professionals have knowledge on the anatomy of the veins and appropriate selection of the sanguine glasses to channel, avoiding flexion areas, likewise almost the entirety of the professionals carries out correctly the steps during and after the canalization suggested in the bibliography. However they are the steps and previous cares to the procedure that the rigurosidad is not completed that demands this way the veined cateterización: 85% doesn't wash his hands; 88.8% is not placed gloves; 96.2% doesn't carry out the asepsis of the area in the time and recommended form; 74% doesn't carry out the cut of excessive body hair to patients that require it; 77% plays other surfaces; and 100% doesn't ask on allergy antecedents to the iodine. Among the complications related with the cateterización of via veined outlying in patients assisted in the investigated services he/she was: obstruction and formation of clots, infiltrations, phlebitis and hematomas.